Body Height and Its Estimation Utilizing Arm Span Measurements of both Gender Adolescents from Central Region in Kosovo - Fitim Arifi; Sami Sermaxhaj; Iber Alaj; Zenel Metaj; Admire Toverlani (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
This study is based on measurements of Central region Kosovar adolescents. The aim of this study was to examine the Body Height of adolescents from Central region as well relationship between arm span and Body Height in both Kosovar genders. A total measured subject participated in this research was 193 out of which (93 girls and 100 boys), females average of age is 18.15±0.35 years old (range 18-20 years) and for male 18.26±0.44 years old (range 18-20 years). The anthropometric measurements were done by trained people and were taken according to the ISAK manual. Relationship between Body Height and arm span has been analyzed by the simple correlation coefficient at a 95% confidence interval. The linear regression analysis was carried out to examine extent to which arm span can reliably predict of Body Height. Statistical importance was placed at level p<0.05. As a result anthropometric measurements for both sexes showed that the average of Body Height for boys adolescents from Central region are 180.62±5.88 centimeters and have the arm span average of 181.36±7.08 centimeters, while girls from Central 166.77±4.71 centimeters tall, and have the arm span average of 167.08±5.03 centimeters. The results have shown that the arm span was estimated as a reliable indicator of Body Height assessment to the both genders adolescents from Central region of Kosovo population. This study also confirms the necessity for developing separate height models for each region in Kosovo.